An overview of the cruise industry in Greece from 2010-2019 - Georgia Papadopoulou (SPOUDAI - Journal of Economics and Business, 2020)
Cruise is one of the most significant sectors worldwide with essential benefits to the economies of the hosting countries and plays a big part in the tourism industry. Cruise tourism develops its tourist activity, as it offers transportation for tourists and at the same time provides accommodation and leisure services. The current study gives an overview of the cruise tourism in Greece from 2010-2019. The year with the higher cruise demand was 2011 and with the lowest 2017. Since 2017 cruise tourism in Greece started to increase in numbers, and this leads to an increase in the income generated by cruise tourism as well.
Keywords: L83; N74; Z32; 330; Cruise tourism; Greece; Expenditures; Cruise passengers; Cruise ships; Arrivals